STUDENT’S PERFORMANCE THROUGH GAMIFICATION IMPLEMENTATION IN TEACHING AND LEARNING ACTIVITIES IN QUANTITY SURVEYING PROGRAMME, UNIMAS - Sitti Diana, Tamjehi (Academia Industry Networks, 2022)
Gamification is one of the most significant innovations in technology for interaction between people. Thus, it is not surprising that gamification has been discussed and introduced especially in the field of education in promoting and sustaining engagement in class. To helps the education sector in implementing the transformation teaching and learning, the gamification is one of the best approaches. In quantity surveying programme, not all courses implement this kind of transformative learning and lack of further research that have been execute. Therefore, this research aim is to obtain student’s performance through gamification implementation in teaching and learning in Quantity Surveying programme. The data collection is gained from the comparison assessment and observation of behaviour among the students during the implementation of game in class. The results shows that students’ performance is very encouraging when gamified the teaching and learning in class. This finding will help educators to review how effective the gamification approach in teaching and learning and produce a variety of games for quantity surveying programme which can help student’s performance.